Optimization formula of instant powder functional drinks from Brunok (Acaudina molpadioides) using foam drying method - R. Marwita Sari Putri; Sri Novalina Amrizal (Akuatikisle: Jurnal Akuakultur, Pesisir dan Pulau-Pulau Kecil, 2020)
This study aims to obtain the right formulation in terms of nutritional and organoleptic value of Brunok instant powder drink. The optimized factor is the amount of Brunok extract used for the manufacture of instant powder drinks with an additional 1% emulsifier and 10% maltodextrin. Making instant powder drinks using the foam mat drying method using an oven with a low temperature setting of 70-80 °C for 15-20 minutes. The use of low temperature is intended to maintain the functional value of the Brunok instant powder drink which is beneficial for health. Based on the trial and error test, 3 instant powder drink formulations were obtained, namely F111, F211 and F311, by means of the hedonic test the preferred formulation for panelists was the F211 formula. The characteristics of the selected powder drink are water content 4.91%, fat 1.75%, protein 2.47%, ash content 0.45% carbohydrate content 90.43% and ALT 7.0x101 colony/g.